PORTARIA MPF/PRM/SGO/ Nº 04, DE 29 DE JUNHO DE 2015 - Maria Beatriz Ribeiro Goncalves (DMPF-e, de 30/06/2015, p.42, 2015)
Institui e regulamenta a atribuição de cada Setor desta Procuradoria da República polo Salgueiro/Ouricuri